MENINGKATAN KEMAMPUAN KOGNITIF MELALUI MEDIA POHON ANGKA PADA ANAK USIA DINI - Rima (GHULAMUNA: JOURNAL OF EARLY CHILDHOOD EDUCATION, 2024)
The aim to be achieved in this research is to find out whether using number trees as a medium can improve the cognitive abilities of class A children at Paud Nazareth, Raja Ampat Regency. The subjects of this research were the research teachers and students in class A of Nazareth Early Childhood Education, Raja Ampat Regency, totaling 9 children with an age range of 4-5 years. The standard value for a process indicator is said to be successful if the results achieved are at least 85%. In cycle I, activity obtained a percentage of 73.33%, then increased to 93.33% in cycle II. Meanwhile, the results of data analysis on students' learning outcomes in initial observations of children's cognitive abilities were 54.54%. After implementing the action, the research results showed that there was an increase in children's learning outcomes in cycle I by 72.73% and increased to 92.85% in cycle II. These results show that at the end of cycle II, there was an increase in children's learning outcomes of 92.85% in the Developing According to Expectations (BSH) category.